Thermosensitive and photocrosslinkable hydroxypropyl chitin-based hydrogels for biomedical applications. (15th July 2018) - Yuan, Meng; Bi, Bo; Huang, Jiachang; Zhuo, Renxi; Jiang, Xulin
Graphical abstract: Highlights: Thermosensitive and photocrosslinkable methacrylated hydroxypropyl chitin synthesized. Injectable and photocrosslinked chitin-based GM-HPCH hydrogels showed high strength. Photocrosslinked GM-HPCH thermogels had tunable degradation and mechanical properties. In situ forming photocrosslinked GM-HPCH thermogels for biomedical applications. Abstract: In situ forming injectable hydrogels based on thermosensitive polymers are being investigated for tissue engineering applications. However, the major limitations of this kind of hydrogels are low gel stability and weak mechanical properties under physiological conditions. Here, thermosensitive hydroxypropyl chitin (HPCH) was synthesized homogenously and subsequently functionalized with photocrosslinkable methacrylate groups via glycidyl methacrylate to generate glycidyl methacrylate-modified HPCH (GM-HPCH). The obtained new GM-HPCH polymers exhibited similar reversible thermosensitive sol–gel transition behaviors at a low concentration (2 wt% in PBS). The physical thermogelation GM-HPCH hydrogels were able to be photocrosslinked by UV irradiation under physiological conditions to form enhanced stable and mechanically strong hydrogels. The mechanical property, swelling and degradation behavior of the hydrogels could be tuned by controlling the degree of substitution of methacrylate groups and UV exposure time. Cytotoxicity test displayed that the photocrosslinked thermogels were non-cytotoxic. The photocrosslinkable GM-HPCH thermogels hold great potential for biomedical applications.